Formononetin isolated from Sophorae flavescentis inhibits B cell-IgE production by regulating ER-stress transcription factor XBP-1 - Yang, Nan; Musa, Ibrahim; Maskey, Anish R.; Li, Ke; Wang, Zhenzhen; Liang, Banghao; Zhang, Shuwei; Zhan, Jixun; Li, Xiu-Min (Frontiers in Allergy, 2023)
RATIONALE: IgE plays an important pathologic role in most, if not all, allergic conditions. We previously showed that ASHMI (anti-asthma herbal medicine intervention) suppressed IgE production in murine models of asthma and in asthma subjects. However, the active compounds in ASHMI responsible for the IgE suppression are still unknown. Objective: We sought to identify the compound (s) in ASHMI that are responsible for IgE inhibition as well as investigate the mechanisms by which the identified compound(s) decreases IgE production. METHODS: The compounds in Sophorae Flavescentis were separated using Column chromatography and preparative-HPLC. The separated compounds were identified using LC-MS and 1H - NMR. U266 cells, an IgE-producing plasma cell line, were cultured with various concentrations of identified compounds. The levels of IgE production by the U266 cell were measured by ELISA. Trypan blue exclusion was used to determine the cell viability. The gene expression of XBP1 and IgE-heavy chain was determined by RT-PCR. RESULTS: A single compound identified as formononetin was isolated from Sophorae Flavescentis. Formononetin significantly and dose dependently decreased the IgE production in U266 cells across a concentration range of 2 μg/mL to 20 µg/mL (p<0.05-0.001 vs untreated cells) with an IC50 value of 3.43 μg/mL. There was no cytotoxicity at any tested concentration. Formononetin significantly decreased XBP1, and IgE-heavy chain gene expression compared with untreated cells (p<0.001). CONCLUSIONS: Formononetin decreased IgE production in human B cell line U266 cells in a dose-dependent fashion through the regulation of XBP1 ER transcription. Formononetin may be a potential therapy for allergic asthma and other IgE-mediated diseases.